Malaysian by-elections: Najib's winning ways - Rashaad Ali (2016)
After the Sarawak state elections and the recently concluded by-elections in peninsular Malaysia, momentum appears to have swung Barisan Nasional’s (BN) way. Has Prime Minister Najib Razak succeeded in regaining support, making calls for snap elections premature?